2011
DOI: 10.1111/j.2044-8309.2011.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

When small losses do not loom larger than small gains: Effects of contextual autonomy support and goal contents on behavioural responses to small losses and small gains

Abstract: Based on the tenets of self-determination theory, the present studies examined the moderating effects of interpersonal contexts or goal conditions that afforded satisfaction of psychological needs on loss aversion effects. We hypothesized that behavioural responses to small losses would be stronger relative to behavioural responses to small gains under goal conditions or interpersonal contexts that did not support psychological needs. We also expected the effect to be minimized under goal conditions or interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Thus, autonomy is likely to increase positive affective and behavioral responses to gain-framed messages and lead to greater motivation to adhere to the recommended health behavior. This proposition is supported by research which showed a reduction in the classic loss aversion effect under conditions of high autonomy [30]. In this experiment, contextual autonomy support (vs. no autonomy support) led to greater persistence on a word task when the gains (vs. losses) of the participant’s previous performance were communicated.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, autonomy is likely to increase positive affective and behavioral responses to gain-framed messages and lead to greater motivation to adhere to the recommended health behavior. This proposition is supported by research which showed a reduction in the classic loss aversion effect under conditions of high autonomy [30]. In this experiment, contextual autonomy support (vs. no autonomy support) led to greater persistence on a word task when the gains (vs. losses) of the participant’s previous performance were communicated.…”
Section: Introductionsupporting
confidence: 57%
“…In addition, following previous research showing that individual differences in autonomy moderate message framing effects for the low-risk preventative health behavior of fruit and vegetable consumption [29], and research suggesting that autonomy supportive context increase response to gain-framed communications [30], we predict that the gain-framed information may be particularly effective under conditions of high autonomy (vs. neutral conditions or those which highlight heteronomy).…”
Section: Introductionmentioning
confidence: 72%
“…Some of the theories that attempt to explain from a psychological point of view the performance of physical activity, include the intention, the motivation to undertake the behavior, as well as the previous attitude of the subjects [31,32]. Moreover, the results found in studies that have related physical activity with other health behaviors, both with American and European samples, indicate that people who engage in some type of physical activity or sports practice, in addition to obtaining physical and psychological benefits, have healthier behaviors than physically inactive people [33,34]. These attitudes, motivations, and intentions are often subject to affective or emotional charges.…”
Section: Physical Activity and Affective Levelsmentioning
confidence: 99%
“…Routine transactions between sellers and buyers also appear to bypass responses to loss aversion (Tversky & Kahneman, 1992) as is observed in experienced stock market traders (Sokol-Hessner et al, 2009). Another boundary condition where the reversal of loss aversion occurs is in contexts that support autonomy (Chatzisarantis, Kee, Thaung, & Hagger, 2012). In other words, when the provision of choice fulfills intrinsic psychological needs, such as autonomy, competence, and interpersonal relatedness (i.e., self-determination theory; Ryan & Deci, 2000), this may induce a stronger positive affect during decision making that may counteract the negative effect of loss of options, leading to a smaller magnitude of loss aversion experienced.…”
Section: Loss Aversionmentioning
confidence: 94%